Neutrophil-to-lymphocyte ratio in pediatric acute appendicitis - Stanković, Nikola D; Stanojević, Ivan; Đorđević, Dragan; Kostić, Zoran; Udovičić, Ivo; Miličković, Maja; Savić, Đorđe; Grujić, Blagoje; Đuričić, Slaviša; Šurbatović, Maja (Vojnosanitetski pregled, 2020)
Background/Aim. Acute appendicitis (AA) is the most frequent emergency and appendectomy is the most frequent abdominal operation in the pediatric surgery. Diagnosis of AA in children is more difficult due to lack of cooperation and poor clinical history data, leading to significant number of misdiagnostic cases. Our aim was to explore whether neutrophil to lymphocyte ratio (NLR) may be useful in diagnosis and follow up of acute appendicitis in children. Methods. Prospective investigation of NLR values in 129 consecutive patients admitted to the Mother and Child Healthcare Institute of Serbia and referred for surgery due to acute appendicitis was performed. According to the pathohistological findings, patients were divided into three groups: normal/early, uncomplicated (phlegmonous) and complicated (gangrenous or/and perforated) acute appendicitis. Laboratory analysis were done preoperativly and on the first and the third postoperative days. Results. Statistically significant differences of NLR values were found in the different time points in total of patients and per groups. Some statistically significant differences of NLR values between pathohistological groups were recorded. Investigations of correlation of NLR and the other laboratory and clinical parameters showed strong positive correlation between NLR and C-reactive protein postoperatively and between NLR and PAS (Pediatric Appendicitis Score) preoperatively. Strong negative correlation with preoperative symptoms duration (PSD) were also present. Optimal cutoff NLR value between negative and positive appendectomies was 6.14. Conclusion. NLR well monitor progression of AA in children, it’s cutoff values may hepl in distinguishing the phases of AA and it should be used in diagnosis of acute appendicitis in children.